Peranan Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen Pengguna E-commerce Shopee Di Politeknik Cendana - Sanny Lonardi; Wong Pong Lan; Fauzi Akbar Maulana Hutabarat; Ngajudin Nugroho; Supriyanto Supriyanto (Journal of Business and Economics Research (JBE), 2021)
The aim of this research is to prove the effect of service quality and price on Shopee e-commerce customer satisfaction at Cendana Polytechnic, either partially or simultaneously. The research method used is associative quantitative method through online questionnaires. The number of respondents/sample as many as 35 students of the Cendana Polytechnic from a population of 408 people with the Accidental Sampling technique. The results showed: (1) Service quality has an influence on Shopee e-commerce customer satisfaction at Cendana Polytechnic, where the T test results, the significant value is 0.005 or less 0.05. (2) price has no effect on Shopee e-commerce customer satisfaction at Cendana Polytechnic, with T-test results, a significant value of 0.105 or greater 0.05. (3) Service quality and price have an influence on Shopee e-commerce customer satisfaction at Cendana Polytechnic with F test results, Fcount 11.488 with F significance of 0.000 or F significance value less than 0.05